PENGARUH TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) TERHADAP RESILIENSI REMAJA USIA 15-18 TAHUN DI SMKN 3 KUDUS - Hellen Novrida; Anny Rosiana Mashitoh; Ashri Maulida (Nusantara Hasana Journal, 2026)
Adolescence is a period characterized by significant physical, emotional, and social changes that make individuals vulnerable to stress and mental health problems. Low levels of resilience among adolescents can lead to anxiety, decreased motivation, poor academic performance, and an increased risk of negative behaviors. Therefore, resilience plays an important role in helping adolescents manage pressure, recover from adversity, and maintain healthy functioning. The Spiritual Emotional Freedom Technique (SEFT) is a relaxation method that combines tapping on the body's meridian points with affirmations and spiritual elements. SEFT has been shown to help reduce stress and anxiety while improving emotional balance. By regulating emotions and promoting a sense of calmness, SEFT has the potential to enhance adolescent resilience. The long-term objective of this study is to develop SEFT therapy as an effective intervention for improving adolescent resilience, thereby reducing stress, anxiety, and emotional mental health problems. The specific objectives include measuring changes in resilience before and after therapy in both intervention and control groups and analyzing the effect of SEFT on resilience improvement. This study employed a quantitative research approach with a pre–post test design involving 52 students selected through purposive sampling. SEFT therapy was administered through the stages of set-up, tune-in, and tapping, while resilience was measured using the Resilience Scale. Data were analyzed using the t-test to determine the effectiveness of the therapy.